PbMC1a/1b regulates lignification during stone cell development in pear (Pyrus bretschneideri) fruit. (1st May 2020) - Gong, Xin; Xie, Zhihua; Qi, Kaijie; Zhao, Liangyi; Yuan, Yazhou; Xu, Jiahui; Rui, Weikang; Shiratake, Katsuhiro; Bao, Jianping; Khanizadeh, Shahrokh; Zhang, Shaoling; Tao, Shutian
Abstract: Programmed cell death (PCD) and secondary cell wall (SCW) thickening in pear fruit are accompanied by the deposition of cellulose and lignin to form stone cells. Metacaspase is an important protease for development, tissue renewal and PCD. The understanding of the molecular mechanism whereby pear ( Pyrus ) metacaspase promotes PCD and cell wall lignification is still limited. In this study, the Metacaspases gene family ( PbMCs ) from P. bretschneideri was identified. PbMC1a/1b was associated with lignin deposition and stone cell formation by physiological data, semiquantitative real-time polymerase chain reaction (RT-PCR) and quantitative RT-PCR (qRT-PCR). Relative to wild-type (WT) Arabidopsis, the overexpression of PbMC1a/1b increased lignin deposition and delayed growth, thickened the cell walls of vessels, xylary fibers and interfascicular fibers, and increased the expression of lignin biosynthetic genes. Yeast two-hybrid (Y2H), bimolecular fluorescence complementation (BiFC) and GST pull-down assays indicated that the PbMC1a/1b protein physically interacted with PbRD21. Simultaneously, the transient expression of PbMC1a/1b and PbRD21 led to significant changes in the expression of genes and lignin contents in pear fruits and flesh calli. These results indicate that PbMC1a/1b plays an important role in cell wall lignification, possibly by interacting with PbRD21 to increase the mRNA levels of some lignin synthesis-associated genes and promote the formation of stone cells in pear fruit.